Subsurface structure of magmatic segments during continental breakup: Perspectives from a gravity data analysis along the Main Ethiopian Rift - Nigussie, Wubamlak; Mickus, Kevin; Keir, Derek; Alemu, Abera; Muhabaw, Yoseph; Muluneh, Ameha A.; Yehualaw, Esubalew; Demissie, Zelalem (Frontiers in Earth Science, 2023)
In magma-rich continental rifts, extension is commonly localized as dike injection in discrete magmatic segments (MSs) which appear from surface geology to mimic the along-axis segmentation of ocean ridges. However, the subsurface morphology of these zones of localized magma injection is unclear, and whether and at what depth range they remain with discrete subvolcanic plumbing systems is not fully understood. In addition, the relationship between zones of magma injection and tectonic faulting is also debated. The Main Ethiopian Rift (MER) provides a unique opportunity to examine the spatial scale, locus, and subsurface geometries of magmatic localization in active continental rifts. We examined spatial variations in the structure of the crust in the MER using gravity data to better understand the subsurface pattern of magma injection. Results of our study reveal discrete Bouguer gravity highs in the centers of the distinct right-stepping MSs of the MER (Aluto, Gedemsa, and Boseti), and interpreted as the locus of mafic intrusions. The gravity data show that the boundary between each MS is observed down to depths of 20 km, suggesting that MSs have discrete subvolcanic plumbing systems at least down to the mid-crust. Additionally, incorporating the fault network shows that the densest faulting occurs at the lateral tips of the zones of densest magma injection shown by Bouguer gravity highs. This is similar to the axial segmentation observed at slow and ultra-slow spreading ridges and suggests strong along-axis variations in deformation mechanism, with magma injection accommodating extension at the segment centers and faulting dominating towards the segment ends. In addition, bilateral rift margin volcanic zones (Siltie Debrezeit, Yerer Tulu, and Galema) are also inferred from bandpass gravity anomaly maps, supported by petrologic evidence, which are attributed to indicate that extension by dike injection has also occured near the rift flanks.